2012
DOI: 10.1111/j.1365-313x.2012.05094.x
|View full text |Cite
|
Sign up to set email alerts
|

A zinc finger protein gene ZFP5 integrates phytohormone signaling to control root hair development in Arabidopsis

Abstract: ). † These authors contributed equally to this work. SUMMARYAlthough root hair development in Arabidopsis thaliana has been extensively studied, it remains unknown whether the zinc finger proteins, the largest family of transcription factors in plants, are involved in this process. Here we report that the C2H2 zinc finger protein ZINC FINGER PROTEIN 5 (ZFP5) is a key regulator of root hair initiation and morphogenesis in Arabidopsis. ZFP5 is mainly expressed in root and preferentially in root hair cells. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 60 publications
1
88
0
Order By: Relevance
“…Cytokinin regulates root system architecture (RSA) by disturbing cell division activity and increasing the length of the root hairs at the root tips [33], [34]. In the present study, we measured the number of lateral roots on the main roots and the average lengths of the root hairs on the root tips of both NIP and the osarf16 mutant under the 0.1 µM 6-BA treatment.…”
Section: Resultsmentioning
confidence: 96%
“…Cytokinin regulates root system architecture (RSA) by disturbing cell division activity and increasing the length of the root hairs at the root tips [33], [34]. In the present study, we measured the number of lateral roots on the main roots and the average lengths of the root hairs on the root tips of both NIP and the osarf16 mutant under the 0.1 µM 6-BA treatment.…”
Section: Resultsmentioning
confidence: 96%
“…For most experiments, seeds were surface-sterilized for 10 min in 30% bleach solution and rinsed five times with sterile distilled water. After vernalization in the dark for 2 d at 4°C, the seeds were germinated and grown vertically on Murashige and Skoog (MS) plates in a growth chamber, as described previously (An et al , 2012). Growth conditions in the chamber were controlled as follows: 22 ± 2°C, 90–120μmol m –2 s –1 , 16h light/8h dark, 68–78% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to auxin and ethylene, our previous research revealed cytokinin as a novel root hair development regulator (An et al , 2012). Application of exogenous cytokinin promotes root hair elongation while lines that overexpress a cytokinin oxidase exhibit a short-hair phenotype (An et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qPCR was conducted in the following cycling conditions: 95°C for 30 s, followed by 40 cycles of 95°C for 10 s and 60°C for 30 s. Melt curve analysis was used to confirm the absence of non-specific amplification products. Relative expression levels were calculated by subtracting the threshold cycle (Ct) values for OsActin (Os03g0718100) from those of the target gene (to give △Ct) and then calculating 2–△Ct as we described before [40][42]. RT-PCR experiments were performed with three biological replicates with the representative being shown.…”
Section: Methodsmentioning
confidence: 99%